ПСИХОЛИНГВИСТИЧЕСКИЕ АСПЕКТЫ ОБРАЗА «ЦВЕТ» В СОЗНАНИИ НОСИТЕЛЕЙ РУССКОГО И УЗБЕКСКОГО ЯЗЫКОВ - Кодирова, Ф.К. (SCIENCE and SOCIETY, 2024)
The article is devoted to the study of the relationship between language and cognitive processes, in particular, the perception of color in two sociolinguistic environments. This work is devoted to comparing the image of "color" in the minds of native speakers of Russian and Uzbek languages. Identifying the relationship between the language system and the cognitive processes of color perception, this article describes the relationship between language and thinking, as well as cultural characteristics of color perception.